EFFECT OF TIN CONTENT AND ECAP PASSES ON THE MECHANICAL PROPERTIES OF Cu/Sn ALLOYS AS BEARING MATERIALS (Port Said Engineering Research Journal, 2014)
Equal channel angular pressing (ECAP) is a materials processing method that allows very high strains to be imposed, leading to extreme work hardening and microstructure refinement. Cast Cu-2, 5 and 10 wt% Sn alloys in the form of 25mm diameter and 300mm long rods are ECAPed through 12 mm diameter, 120o inner angle, and 20o out arc angle die. It is possible to ECAP those alloys for 5, 4, and 1 pass at room temperature, respectively. Grain size decreases of with increasing Sn content and number of ECAP passes. Besides, the ultimate tensile stress, proof strength, and hardness of Cu-2, 5 and 10%Sn alloys increase with Sn content and ECAP pass number. However, UTS of 2%Sn alloy reaches a maximum value after 4 passes, and that of 5%Sn alloy reaches its maximum after 3 passes. Moreover, the elongation percent decreases strongly after first ECAP pass. The elongation of Cu-2 and 5%Sn alloys begin to increase after second pass until third and fifth passes, respectively. On the other hand, the wear resistance is improved by increasing Sn content and number of ECAP pass, especially after first pass. Also, remarkable decrease is observed in surface roughness (Ra) by decreasing Sn content and by increasing the number of ECAP pass.